Answer:
Step-by-step explanation:
27 ) 2x² - x - 1 = 0
2x² - 2x + x - 1 = 0
2x ( x - 1) + (x - 1) = 0
(x - 1)(2x + 1) = 0
x - 1 = 0 ; 2x + 1 = 0
x = 1 ; 2x = -1
x = -1/2
x = 1 ; -1/2
Option b
28) Area of a rectangle = 24 cm²
length * width = 24
(3x +2 )(2x -1) = 24
3x(2x -1) + 2(2x - 1) = 24
3x *2x - 3x *1 + 2*2x - 2*1 = 24
6x² -3x + 4x - 2= 24
6x² + x - 2 -24 = 0
6x² + x - 26 = 0
6x² -12x + 13x - 26 = 0
6x(x - 2) + 13(x - 2) = 0
(x -2)(6x +13) = 0
x = 2 {Ignore 6x + 13 as it gives negative value}
length = 3x + 2 = 3*2 + 2 = 6 + 2 = 8 cm
Width = 2x - 1 = 2*2 - 1 = 4 - 1 = 3 cm
29) Area of square = 900 cm²
Side² = 900
(5x)² = 900
25x² = 900
x² = 900/25
x² = 36
x = √36 = √6*6
x = 6 cm
30) base = b cm
height = b + 2
Area of triangle = 24 cm²
![\dfrac{1}{2}base*height = 24\\\\\dfrac{1}{2}*b*(b+2) = 24\\](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7B2%7Dbase%2Aheight%20%3D%2024%5C%5C%5C%5C%5Cdfrac%7B1%7D%7B2%7D%2Ab%2A%28b%2B2%29%20%3D%2024%5C%5C)
b(b + 2) = 24*2
b² + 2b = 48
b² + 2b - 48 = 0
b² - 6b + 8b - 48 = 0
b(b - 6) + 8(b - 6) = 0
(b - 6) (b + 8) = 0
b - 6 = 0 {Ignore b +8 = 0 as it gives negative value}
b = 6 cm
height = 6+ 2 = 8 cm
I think it would be conditional, because B depends on A. Of A is false, then B isn’t possible, making it conditional.
Answer:
A) f(x) = 6x + 14
Step-by-step explanation:
6(1) + 14 = 20
6 + 14 = 20
6(1.5) + 14 = 23
9 + 14 = 23
6(2) + 14 = 26
12 + 14 = 26
and so on...
Answer:
a kite
Step-by-step explanation:
because the question asks what special quadrennial is formed by connecting the midpoints